Kajian Budaya Fotografi Potrait dalam Wacana Personalitas - Andang Iskandar; Cece Sobarna; Deddy Mulyana; Yuyu Yohana Risagarniwa (PANGGUNG, 2014)
ABSTRACT Portrait Photography is a representation of similarity in the form of two-dimensional human fi- gure. Portrait photography gives a personal good indication of the owner’s portrait, portrait subjects and photographers. Personality photographic work representing one’s personal character. This study aims to explain the problems of cultural studies in the discourse on photography portrait personality. This research method using literature review of the literature both books, journal articles and research reports, especially portrait photography in cultural studies. The study provides an overview of cul- tural studies on four issues for portrait photography: first, photography as a representation. Portrait is where negotiations between the photographer with the subject of self-representation (model). Se- cond, diaspora photographers. Photographers Indonesian Chinese (Peranakan) as cultural brokers in the post-colonial period. The diﬀerence between the Peranakan culture and totok also distinguished in the profession of social groups in studio photography. Third, the identity of the portrait. Family’s photo album as a way structured ourselves, and cultural identities through ritual memory. Fourth, photography as a medium of cultural domination. Photography is a meaning synthesis of subject and object photos. Keywords: cultural studies, portrait photography, personality, discourse  ABSTRAK Fotografi potrait merupakan representasi kemiripan figur manusia dalam bentuk dwimatra. Fotografi potrait memberikan indikasi personal baik pada pemilik potrait, sub- jek potrait maupun fotografer. Personalitas karya fotografi yang mewakili pribadi bahkan karakter seseorang. Penelitian ini bertujuan untuk menjelaskan permasalahan kajian buda- ya pada fotografi potrait dalam wacana personalitas. Metode penelitian ini menggunakan metode kajian pustaka dari berbagai literatur baik buku, artikel jurnal dan laporan pene- litian fotografi khususnya potrait dalam kajian budaya. Hasil penelitian ini memberikan gambaran empat permasalahan kajian budaya pada fotografi potrait yaitu pertama, foto- grafi sebagai representasi. Potrait merupakan tempat negosiasi antara fotografer dengan representasi-diri subjek (model). Kedua, diaspora fotografer. Fotografer China Indonesia (peranakan) sebagai broker budaya di masa poskolonial. Perbedaan budaya antara per- anakan dan totok dibedakan juga dalam kelompok sosial profesi dalam studio fotografi. Ketiga, identitas dalam potrait. Album foto keluarga sebagai sebuah cara untuk menstruk- turisasi diri, identitas dan budaya melalui ritual ingatan. Keempat, fotografi sebagai me- dia dominasi budaya. Fotografi adalah sintesis pemaknaan dua subjek yang-memotret dan yang-memandang. Kata kunci: kajian budaya, fotografi potrait, personalitas, wacana